Evolutionary and taphonomic implications of a new species of Amphoracrinus from the early Viséan of Kentucky. (November 2021) - Ausich, William I.; Koenig, Steven C.; Goldstein, Alan; Monreal, Gretel
Abstract: The youngest species of Amphoracrinus, A. tenax new species, is described from the Muldraugh Member of the Borden Formation (early Viséan) of north-central Kentucky. With this new occurrence, both the oldest and youngest named species of Amphoracrinus are from North America. Numerous Tournaisian and Viséan crinoid faunas are documented in the United States, but only four are known to contain Amphoracrinus . Morphological analysis indicates that A. tenax is more closely aligned with species from China than with species from Western Europe or other species from North America, where Amphoracrinus was most diverse and abundant, which has implications for understanding paleogeographic dispersal. The holotype of A. tenax was partially disarticulated on the seafloor before burial, and final burial occurred early during disarticulation. The relative state of disarticulation from pinnules to columnals suggests that plates bound only with ligaments disarticulated as a function of surface area of ligaments binding an articulation. UUID: http//zoobank.org/c7faf06e-bdd1-43a2-8c10-1364a0aeae0d